Effects of sequential ethanol exposure and repeated high-dose methamphetamine on striatal and hippocampal dopamine, serotonin and glutamate tissue content in Wistar rats. (5th February 2018) - Almalki, Atiah H.; Das, Sujan C.; Alshehri, Fahad S.; Althobaiti, Yusuf S.; Sari, Youssef
Highlights: Reduction of dopamine and 5-HT in ethanol/METH group in striatum/hippocampus. Increased glutamate levels in ethanol/METH group in striatum. Decreased glutamate levels in Ethanol/METH group compared to METH in striatum. Abstract: Alcohol (ethanol) and methamphetamine (METH) co-abuse is a major public health issue. Ethanol or METH exposure has been associated with changes in neurotransmitter levels in several central brain regions. However, little is known about the effect of sequential exposure to ethanol and METH on glutamate, dopamine and serotonin tissue content in striatum and hippocampus. In this study, we investigated the effects of sequential exposure to ethanol and METH on tissue content of these neurotransmitters. Male Wistar rats were orally gavaged with either ethanol (6 g/kg) or water for seven days. Rats were administered with high dose of METH (10 mg/kg, i.p. every 2 h × 4) or saline on Day 8 and euthanized 48 h of last METH or saline i.p. injection. In the striatum, sequential exposure to ethanol and METH increased glutamate tissue content while reducing dopamine and serotonin tissue content as compared to the group exposed to ethanol alone. In the hippocampus, sequential exposure to ethanol and METH decreased serotonin tissue content as compared to the group that was exposed to ethanol alone. However, this study showed that ethanol has no additive effect to METH on tissue content of dopamine and serotonin as compared to METH in the striatum and hippocampus. This study demonstrated that sequential exposure of ethanol and METH has an additive effect on tissue content of certain neurotransmitters in the brain.